Protective role of rosmarinic acid on amyloid beta 42-induced echoic memory decline: Implication of oxidative stress and cholinergic impairment. (September 2018) - Kantar Gok, Deniz; Hidisoglu, Enis; Ocak, Guzide Ayse; Er, Hakan; Acun, Alev Duygu; Yargıcoglu, Piraye
Abstract: In the present study, we examined whether rosmarinic acid (RA) reverses amyloid β (Aβ) induced reductions in antioxidant defense, lipid peroxidation, cholinergic damage as well as the central auditory deficits. For this purpose, Wistar rats were randomly divided into four groups; Sham(S), Sham + RA (SR), Aβ42 peptide (Aβ) and Aβ42 peptide + RA (AβR) groups. Rat model of Alzheimer was established by bilateral injection of Aβ42 peptide (2, 2 nmol/10 μl) into the lateral ventricles. RA (50 mg/kg, daily) was administered orally by gavage for 14 days after intracerebroventricular injection. At the end of the experimental period, we recorded the auditory event related potentials (AERPs) and mismatch negativity (MMN) response to assess auditory functions followed by histological and biochemical analysis. Aβ42 injection led to a significant increase in the levels of thiobarbituric acid reactive substances (TBARS) and 4-Hydroxy-2-nonenal (4-HNE) but decreased the activity of antioxidant enzymes (SOD, CAT, GSH-Px) and glutathione levels. Moreover, Aβ42 injection resulted in a reduction in the acetylcholine content and acetylcholine esterase activity. RA treatment prevented the observed alterations in the AβR group. Furthermore, RA attenuated the increased Aβ staining and astrocyte activation. We also found that Aβ42 injection decreased the MMN response and theta power/coherence of AERPs, suggesting an impairing effect on auditory discrimination and echoic memory processes. RA treatment reversed the Aβ42 related alterations in AERP parameters. In conclusion, our study demonstrates that RA prevented Aβ-induced antioxidant-oxidant imbalance and cholinergic damage, which may contribute to the improvement of neural network dynamics of auditory processes in this rat model. Highlights: Aβ42 affects antioxidant-oxidant balance and cholinergic system. Aβ42 causes deficit in network dynamics of auditory system. Rosmarinic acid reverses the Aβ42 induced alterations in auditory functions. Cholinergic enhancement via rosmarinic acid might be useful in AD. Rosmarinic acid might be efficient in AD treatment with its multiple bioactivities.